Actinomyces cardiffensis sp. nov. from Human Clinical Sources - Hall, Val (American Society for Microbiology, 2002)
Eight strains of a previously undescribed catalase-negative Actinomyces-like bacterium were recovered from human clinical specimens. The morphological and biochemical characteristics of the isolates were consistent with their assignment to the genus Actinomyces, but they did not appear to correspond to any recognized species. 16S rRNA gene sequence analysis showed the organisms represent a hitherto unknown species within the genus Actinomyces related to, albeit distinct from, a group of species which includes Actinomyces turicensis and close relatives. Based on biochemical and molecular genetic evidence, it is proposed that the unknown isolates from human clinical sources be classified as a new species, Actinomyces cardiffensis sp. nov. The type strain of Actinomyces cardiffensis is CCUG 44997(T).